2011
DOI: 10.1021/bi201449r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Purified New Delhi Metallo-β-lactamase-1

Abstract: New Delhi metallo-β-lactmase-1 (NDM-1) has recently emerged as a global threat because of its ability to confer resistance to almost all clinically used β-lactam antibiotics, its presence within an easily transmissible plasmid bearing a number of other antibiotic resistance determinants, its carriage in a variety of enterobacteria, and its presence in both nosocomial and community-acquired infections. To improve our understanding of the molecular basis of this threat, NDM-1 was purified and characterized. Reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
189
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(209 citation statements)
references
References 56 publications
20
189
0
Order By: Relevance
“…Furthermore, the kinetic assay indicated that NDM-1 showed approximately 2-fold increase of hydrolytic activity on ampicillin and meropenem in the presence of 50 M ZnSO 4 compared to the condition in the absence of zinc in the assay buffer (data not shown). Our kinetic constants determined under our assay condition supplemented with 50 M ZnSO 4 were similar to those of other reports (25), suggesting that under our assay condition, the NDM-1 protein was likely in its dizinc form.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the kinetic assay indicated that NDM-1 showed approximately 2-fold increase of hydrolytic activity on ampicillin and meropenem in the presence of 50 M ZnSO 4 compared to the condition in the absence of zinc in the assay buffer (data not shown). Our kinetic constants determined under our assay condition supplemented with 50 M ZnSO 4 were similar to those of other reports (25), suggesting that under our assay condition, the NDM-1 protein was likely in its dizinc form.…”
Section: Resultssupporting
confidence: 88%
“…S2C in the supplemental material). It is widely accepted that a hydroxide/water between Zn1 and Zn2 is ready for the nucleophilic attack in a binding geometry where the carbonyl oxygen of the ␤-lactam ring associates with Zn1, while one of the carboxylate oxygens of the fused ring coordinates with Zn2 (14,17,25,26). The approach of molecular docking following the suggested binding mode of ␤-lactam moieties to two Zn ions enabled us to model the promising structures of NDM-1 with different cephalosporins.…”
Section: Resultsmentioning
confidence: 99%
“…The final assay solution used to monitor ampicillin hydrolysis (as described above) contained 0.3 mL of 50 mM Hepes, pH 7, 0.6 mM ampicillin, 20 nM NDM variant, with addition of ZnSO4 to the final concentrations of 0.0001, 0.01, 0.1, 0.5, 1, 5, 10, 50, and 100 µM. Observed rates were converted into percentages, using the highest value for each variant as 100 %, as described earlier (5,16). Since most NDM variants showed increasing activity followed by a loss of activity as zinc concentrations were increased, data were fitted using the equation below, with [Zinc] being the concentration of ZnSO4, x being the activity (%) at no added zinc, y being the Kd,Zn2, and z being Kd for binding an inhibitory zinc at high concentrations.…”
Section: Fluorescencementioning
confidence: 99%
“…It is commonly suggested that the zinc ion acts as a Lewis acid to stabilize the transient tetrahedral intermediate formed by the nucleophilic attachment of a hydroxide ion to the carboxyl group of the ␤-lactam ring (10). NDM-1 enzyme shows a great ability to hydrolyze all ␤-lactam antibiotics (11). Several crystal structures of NDM-1 have been solved, and the enzyme displays the typical ␣␤/␤␣ fold of MBLs (12,13,14).…”
mentioning
confidence: 99%